2017
DOI: 10.1007/s10396-017-0837-y
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave elastography evaluation in pediatric testicular microlithiasis: a comparative study

Abstract: SWE evaluation demonstrates the effects of ultrastructural changes in elasticity that are not detected on gray-scale ultrasound. SWE is a more reliable method in follow-up examinations for pediatric testicular microlithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The feasibility and efficiency of SWE in detecting ultrastructural changes in testicular parenchyma in various diseases have been demonstrated in previous reports [ 5 - 7 ]. Furthermore, several studies have focused on the impact of varicocele on the testes using elastography.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The feasibility and efficiency of SWE in detecting ultrastructural changes in testicular parenchyma in various diseases have been demonstrated in previous reports [ 5 - 7 ]. Furthermore, several studies have focused on the impact of varicocele on the testes using elastography.…”
Section: Discussionmentioning
confidence: 93%
“…However, volumetric changes in testes with varicocele might manifest at a later stage of the disease, and testicular volume might not be an ideal surrogate marker of underlying ultrastructural changes in the testes. The feasibility and efficiency of SWE in detecting ultrastructural changes in testicular parenchyma in various diseases have been demonstrated in previous reports [5][6][7]. Furthermore, several studies have focused on the impact of varicocele on the testes using elastography.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Another study investigated TML in 9 young patients and found that the mean testicular volume did not differ from the control group 17 . Bayramoglu et al investigated testicular volume in 23 pediatric patients with TML and 31 pediatric patients without TML, and found no difference in testicular volume between the study and control groups 18 . However, it is possible that ethnicity also affects testicular volume 19 .…”
Section: Discussionmentioning
confidence: 97%
“…The diagnostic usefulness of testicular sonoelastography has been investigated in multiple studies on undescended testis, testicular microlithiasis, scrotal hydroceles, testicular torsion, and malignant tumors [5][6][7][8][9]. Several previous studies found that varicoceles change the testicular stiffness measured by elastography [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%